Maternal Mentalization and Behavior Under Stressful Contexts: The Moderating Roles of Prematurity and Household Chaos. (6th March 2018) - Yatziv, Tal; Gueron‐Sela, Noa; Meiri, Gal; Marks, Kayla; Atzaba‐Poria, Naama
Abstract : This study examines the links between online maternal mentalization during mother–infant interaction, maternal sensitivity, and family triadic interaction while considering the cumulative role of two stressful contexts (cumulative stressful contexts): premature birth (a child‐driven stressful context) and household chaos (an environment‐driven stressful context). Two moderation models were tested on a sample of 134 families with 6‐month‐old infants (77 low‐risk preterm, 57 full‐term). Cumulative stressful contexts mitigated the relations between maternal mentalization and behavior, such that online maternal mentalization during mother–infant interaction was related to both maternal sensitivity and the quality of family triadic interaction under low cumulative stressful contexts, but not under high cumulative stressful contexts. Implications for understanding the influence of online maternal mentalization on maternal sensitivity and the family triad are discussed.